Ozone photolysis: Strong isotopologue/isotopomer selectivity in the stratosphere. Issue 7 (9th April 2014) - Ndengué, Steve; Madronich, Sasha; Gatti, Fabien; Meyer, Hans‐Dieter; Motapon, Ousmanou; Jost, Rémy
Abstract We calculated the photolysis rate coefficients of five ozone isotopologues/isotopomers as functions of altitude up to 80 km using recent ab initio absorption cross sections and an averaged actinic flux. Three of the five ozone isotopologues/isotopomers are symmetric, with a single isotopic dissociation channel, and two are asymmetric with two isotopic dissociation channels. The specific contributions of the Chappuis, Huggins, and Hartley bands to the photolysis rates and enrichments have been determined as a function of altitude. The Chappuis and Hartley bands have a dominant contribution to the photolysis rates, respectively at low and high altitudes, but these two bands are characterized by small fractionations. In contrast, the Huggins band has a minor contribution to the overall photolysis rate at any altitude, but it generates most of the strong fractionation which peaks around 35 km. The photolysis fractionations are "mass dependent" in contrast with those due to the ozone formation process which are "non–mass dependent." The altitude dependences of our photolysis fractionations are in qualitative agreement with those of Liang et al. (2006) but differ quantitatively, most notably because the contribution of the Huggins band has been reevaluated. The branching ratio between the two electronic dissociation channels (either O(3P) or O(1D) products) has been used to calculate the isotopic enrichments of the reactive O(1D) induced by ozone photolysis. The isotopic photolysis rates can be included in a global kinetic model that includes ozone formation processes and collision with O2 and other oxygen‐containing species.